Teknologi Tepat Guna e-Government KOTIM Untuk Administrasi Keuangan (Studi Kasus Desa Sumber Makmur Kecamatan Telawang) Berbasis Website - Rahmadi Muhammad; Depi Rusda (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2020)
Abstract : Sumber Makmur Village is one of 6 (six) villages located in Telawang Subdistrict, East Kotawaringin Timur, Kalimantan Tengah Province, Indonesia. The residents in Sumber Makmur Village are transmigrants from Java, Sumatra and local transmigration participants who occupy a land area of 4,014.15 hectares. In general, the problems faced by the community in Sumber Makmur Village today are in terms of accessing information in the village, both information on activities carried out by the village, information on village development and information on APBDes so that usually people have to come directly to the village office to get it. So to overcome the above problems, a website-based information system is needed, so that people no longer need to come to the village office just to ask for this information but by accessing the village website the community can get it directly and for the village with the village website it can certainly make it easier for them to sharing information without creating information boards that are placed in front of the village office. Furthermore, to create a website-based information system, a Macromedia Dreamweaver programming language editor software is needed with the PHP programming language, Cascading Style Sheet (CSS), JavaScript and MySQL database.